Enteric Parasitic Infections among School Children at Rupandehi, Nepal - Khanal, Rita; Upadhaya, Sweety; Lamichhane, Pramila; Karn, Subash Lal; Pokhrel, Sandeep; Pahwa, V. K. (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Soil-transmitted helminths (STHs), are the common intestinal parasites among school age children in Nepal. Periodic epidemiological studies and transmission dynamics in parasitic infections will provide accurate understanding. The aim of this study is to find out the prevalence of intestinal parasitic infections among primary school children at Rupandehi district Nepal. MATERIALS AND METHODS: This is a school based cross-sectional descriptive study including 217 students studying at primary level in two Government School in Rupandehi. The demographic data and anthropometric data was collected. Routine Stool examination was done and concentration techniques were used for maximum recovery of parasites. RESULTS: The prevalence of parasitic infection was 60% (130/217). Statistically significant association was found between parasitic infection and source of drinking water (p<0.05) A. lumbricoides was most common followed by Taenia spp, Hymenolepsis nana and others. Parasitic infection was highest 70% (21/30) in age group 13-15 years and lowest i.e. 38.1% (8/21) in age group 4-6 years. The mean height and weight of children was found to be 1.28 m and 26.5 kg respectively. Among total children 90.8% (197/217) of the children were malnourished (BMI<18.5 kg/m2) and among infected children 90% (117/130) were malnourished. CONCLUSION: The intestinal parasitosis was found comparatively higher in school children in this region. Higher rate of infection was found in malnourished children. Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 30-34